ANALISIS JENIS KERANG (PELECYPODA/BIVALVIA) DI KAMPUNG AMBAI DISTRIK KEPULAUAN AMBAI KABUPATEN KEPULAUAN YAPEN - Ortis F Waromi; Zainal A. Wasaraka; Daniel Lantang (Universitas Cenderawasih, 2016)
ABSTRACTThis study aims to determite the types of shells contained in Ambai village, Ambai Island District, Yapen Island Regency, to know what kind of shellfis is utilized by the community of Ambai village, to know the diversity of species of shell found on the beaches of Ambai village, Ambai Island District, Yapen Island Regency, and to know how the habitat charteristics for the type of shell (Pelecypoda/Bivalvia) in the village of Ambai. This research was conducted on three stations. The method used in this reseach is line tansect method white data analysis is done descriptively and quantitatively, and to know the diversity of type using Shnnon wiener diversity index. The resultas of study found eleven types of (Pelecypoda/Bivalvia) consist of six families located at the reseach location of the type Vepricardium sinense (Cardiidae), Polymesoda cauxaus, Polymesoda bengalensis (Corbiculidae), Hiatula chinensis (Psammobiidae), Meretrix meretrix, Gafrarium tumidum, Gafrarium pectinatum, Periglypta reticulata (Veneridae), Anadara antiquata, Barbatia decussata (Arcidae), Tellina virgata (Tellinade). The shellfish used by the community of Ambai village consist of four types namely type Polymesoda cauxaus, Polymesoda bengalensis, Anadara antiquata, and Meretrix meretrix. In transect I was fornd characteristic type of muddly sand substrate, transect II and III type of substrate of muddly sand fine sand, nested sand. With the diversity index of shellfish species located in the beach of Ambai village, Ambai Island District Yapen Island Regency is H’=1, Can be categorized as low. Key words : Shellfish (Pelecypoda/Bivalvia), Ambai village.